History of vaccine development editor. - Plotkin, Stanley A.; SpringerLink (Online service). (New York Springer, 2011)
The history of vaccines now goes back over 300 years to the work of Jenner but the last 50 years have seen an enormous acceleration of the pace of vaccine development and, accordingly, the impact on infectious diseases. However, no vaccine development has been easy and there is an interesting story attached to each. The editor of this book brought together a number of the scientists responsible for modern vaccines and historians familiar with the stories about the ones developed in earlier centuries. The chapters in this book recount the hard work and detours that are intimately associated with vaccine development and give some sense of the perseverance that gave public health the tools of modern preventive medicine.
Electronic reproduction.
Keywords: Vaccines -- Design -- History; Vaccination -- History; Electronic books